Existentialism in the Characterization of the Main Character in the Novel Joseito - Nursoufiliani, Fhoeby; Febrianty, Fenny (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The novel “Joseito” by Osamu Dazai depicts the complex journey of a high school student caught in an existential dilemma. This study aims to conduct an in-depth analysis of the themes of existentialism revealed in the novel. The purpose of this study is to understand how the novel “Joseito” reflects the concepts of existentialism, such as the search for meaning, loneliness, loss, and individual freedom. The method applied is descriptive qualitative research, with steps that include data provision through reading and note-taking techniques, data analysis through grouping data into relevant categories, and presentation of data analysis results. The results of this study show that the novel “Joseito” deeply depicts the main character's existential struggle in the face of uncertainty and internal conflict. The conclusion of this research is that the novel “Joseito” by Osamu Dazai successfully depicts the themes of existentialism well through the main character, which reflects the struggle of human beings in facing their existence in the modern world full of social pressure and individual anxiety.